Rookie Reader : Harry's Hats - Tompert, Ann; 1953-; Elizalde, Marcelo (New York, 2004)
A young boy has fun doing different activities depending on the hat he is wearing each day of the week.
Accelerated Reader AR
Keywords: Children; Hats; Early reader